Mathematical Modeling of Air Pollution After a Quarry Explosion: Express Forecast - Medvedieva, O. O.; Biliaieva, V. V.; Kirichenko, P. S.; Kozachyna, V. A.; Usenko, A. Yu. (Science and Transport Progress, 2025)
Purpose. Development of a CFD model that makes it possible to quickly predict the level of dust pollution of atmospheric air after an explosion in a quarry, development of a fast CFD calculation model. Methodology. To solve the aerodynamics and mass transfer problem, the fundamental equations of continuum mechanics are used. The air flow velocity field is modeled using the Laplace equation for the velocity potential. Numerical integration of the Laplace equation is carried out using the splitting method. After splitting, difference equations are constructed that can be solved by an explicit formula. The G. Marchuk model is used to model the distribution of dust in atmospheric air. Difference splitting schemes are used for numerical integration of the mass transfer equation. At the first stage, physical splitting is carried out into the equations of diffusion and convective dust transport. Then, alternating triangular difference splitting schemes are constructed. The terrain is modeled on a rectangular difference grid using markers. Findings. A set of numerical models has been developed to solve the problems of aerodynamics and mass transfer of a significant impurity in atmospheric air. Finite-difference splitting schemes have been used to build numerical models, which allow obtaining simple calculation dependencies. The constructed numerical models make it possible to quickly calculate the dynamics of dust pollution in conditions of complex terrain. Originality. Numerical models have been built to analyze the dynamics of dust pollution of atmospheric air after an explosion in a quarry. The model makes it possible to take into account the geometric shape of the relief, weather conditions, the rate of gravitational dust deposition, atmospheric diffusion, and the shape of the dust cloud after the explosion. The model can be used for rapid assessment of the impact of explosions on the environment. Practical value. A specialized package of computer programs has been developed to conduct a computational experiment based on the constructed numerical models. The results of the numerical experiment are presented.